HUMOUR AND SATIRE W.SHAKESPARE’S COMEDIES - Rayimova Shahina Shermat qizi; Khamitov Eldorbek Erkin O’g’li (TADQIQOTLAR.UZ, 2024)
ABSTRACT. This article will discuss a brief summary of the information learned about the humorous scenes as well as satire in his works. The plays exploration of love, deception, and self-discovery are infused with wit and irony, highlighting Shakespeare's ability to use humor as a tool for social commentary.